The Impact of the International Accounting Convergence on Income Smoothing in Brazillian Companies - Roberto Carlos Klann; Ilse Maria Beuren (BBR: Brazilian Business Review)
In Brazil, the converg ence to IASB standards began in 2008 with the entry into force of the Lawn. 11.638/07. This study has as objective to verify the influence of the convergence process to the international accounting standards in income smoothing level in Brazilian companies. The study has a quantitative approach, based on the model of Barth, Landsman and Lang (2008), was carried out from the financial statements of 133 companies in the period of 2005-2007 (pre -IFRS) totaling 344 observations, as well as 106 companies in the period of 2010 - 2012 (post-IFRS), totaling 289 observations. The financial statements were extracted from Thomson ONE Banker website. In the data analysis, were applied statistical techniques of multivariate linear regression, Ftest and Pearson correlation. The results show a rising in income smoothing levels after convergence. It is concluded that the effectiveness of the process of convergence of accounting standards of the country to international standards, in order to get better quality of accounting information, does not depend only on the convergence of accounting standards.